Do Working Capital Strategies Matter? Evidence from Small Business Data in Japan1. (16th December 2018) - Tsuruta, Daisuke
Abstract: Previous studies show that a high level of working capital is harmful to firm performance. Using data from over 100, 000 small businesses in Japan, we show that a high level of working capital has a positive effect on default risk and sales growth. Therefore, this activity has both positive and negative effects. Additionally, the relationship between working capital and firm performance is negative over a 1‐year period, but positive over longer periods, implying that a high level of working capital is ultimately not harmful for small businesses.